The use of littoral benthic macroinvertebrates of the Martín Garcia Island Nature Reserve as indicators of water quality - César, Inés Irma (2019)
At Martín García Island—a Natural Reserve located at the confluence of the Paraná and Uruguay rivers—we used benthic-macroinvertebrate biotic indices to elucidate the structure and community parameters of the littoral benthos and their response to environmental variables and to evaluate the island's coastal water quality. Seasonal campaigns were carried out (March/1995-March/1996) at eight sites of the island's littoral sites, selected according to the substrate characteristics (fine sands, sandy-silty, reedbed, and silty with great hydrophyte development). From the sites with a soft substrate, triplicate samples were extracted using a 225-cm2 Ekman manual dredge. The relative abundances of 71 taxa were measured: Nematoda, Turbelaria, Oligochaeta (23 sps.), Mollusca (21 sps.), Crustacea (11 sps.), Insecta (12 families), and Tardigrada. Macroinvertebrate density: 15-58,800 ind.m-2. Analysis of variance revealed significant differences between the average annual macroinvertebrate-population densities among the five sites (F: 3.059; p<0.05). Site 7 exhibited the highest density at 38,700±19,000 ind.m-2 Community parameters: diversity (H'; 0.77-2.16 bits); equitability (J; 0.16-1.02), and species richness (S; 3-29). Canonical-correspondence analysis indicated the environmental variables experiencing the greatest fluctuation to be: dissolved-oxygen concentration, pH, temperature, and conductivity. The results of this analysis suggest that macroinvertebrate-species distribution involves the physicochemical conditions of the water. Of the correlation between species and environmental variables, 95.5% were distributed on the canonical-correspondence ordering diagram's Axis 1. Functional feeding groups: In all sites and seasons, the gathering collectors predominated, followed by the scrapers, filtering collectors, shredders, and predators. Macroinvertebrate Index of Pampean-Rivers: values generally ranged from weak to weak-to-very-weak to zero pollution, but there was a high degree of pollution (2.4 and 1.5) in the spring of 1995.